Determination of Stock Option Prices Using the Black Scholes Method On Stocks Listed On the Jakarta Islamic Index for The Period 2021 - 2022 - Assyamsi, Alghifari; Agustina, Nina; Fauziah Ani; Manaf, Chaerudin (Journal of Social Transformation and Regional Development, 2023)
The capital market is one of the investment instruments favored by the Indonesian people. Reporting from KSEI, the number of investor growth from 2019 to 2022 continues to increase. Recorded in 2019 the number of capital market investors in Indonesia reached 2,484,354 and at the end of the listing on November 3, 2022 the number of capital market investors in Indonesia reached 10,000,628. The purpose to be achieved in this study is to find out and explain the calculation of the value of call options with weekly company stock data in order to find out which stocks are suitable for hedging and decisions that can be made based on the data that has been calculated. The type of research used is descriptive research with a quantitative approach. The sample taken amounted to 12 companies obtained based on determining the criteria in the form of increasing shares seen from the company’s trend line during 2021-2022. The calculation method used is Black-Scholes by utilizing Microsoft Excel. The results showed that by using the Black Scholes method in determining option contracts, some stocks in certain semesters are not recommended to use call option contracts because the option price is zero (0), such as INCO shares in semester 2, PTBA shares in semester 4, TLKM shares in semester 3, and UNTR shares in semester 2. The results of the comparison of the Black Scholes stock option contract with the JCI call option contract show that ADRO, AKRA and PTBA shares can provide the highest profit for investors when using the Black Scholes method because they have a lower call option contract value than the market value. ADRO, AKRA and PTBA stocks have a positive purchase option contract difference value of 3 semesters so that they can provide the highest profit for investors.